The analytic expressions of signal linear parts for fiber-optic reflective system - Kleiza, Vytautas; Kleiza, Jonas (Lietuvos matematikos rinkinys, 2005)
In this work the analytic expressions of absolute maxima and dislocation of signal linear parts for family of signals curves for fiber-optic reflective system have found.